Documentary Video Media Development on Food Additives - Sabdaningtyas, Katherina; Hairida, Hairida; Rasmawan, Rahmat; Masriani, Masriani; Hadi, Lukman (Universitas Pendidikan Mandalika, 2024)
In this era, technology is advancing and developing rapidly. Almost every minute or even second we are in direct contact with technology. In today's world of education, it is also inseparable from the role of technology. Students who on average have good technological literacy tend to get bored more quickly when learning runs conventionally. Regarding the function of learning media, it can be emphasized as follows: as a tool to streamline learning, accelerate the teaching and learning process, and improve the quality of the teaching and learning process. The purpose of this research is to produce a documentary video about food additives that is expected to be utilized for ease of learning. The method used in this research is research and development developed by Borg and Gall. This documentary video media development procedure goes through stages, namely: (1) Research and information gathering, (2) Product development planning, and (3) Initial Product Development. Data or information collection techniques using literature studies and field studies. Stages of video development by creating a storyboard using a video editor application. The next stage of learning videos is validated or evaluated by experts.Â This Documentary Video validation analysis uses descriptive methods through questionnaires. The results of the validation of this Documentary Video obtained an average score of 3.5 by entering the valid category. It can be concluded that this Video Documentary is suitable for use and can be followed up by looking at student responses.